Perioperative Coagulopathy in Patients with Normal Preoperative Coagulation Screen: A Couple of Coagulopathic Clinical Case Conundrums - Monteiro, Joseph N.; Goraksha, Shwetal; Dhokte, Ninad S.; Padate, Balkrishna (Journal of Neuroanaesthesiology and Critical Care, 2020)
Perioperative coagulopathy impacts patient outcome by influencing intraoperative hemodynamics and blood loss. We present two cases which despite having normal preoperative coagulation profiles and normotension during the surgery had intraoperative coagulopathy and unusual bleeding. These cases required a multidisciplinary approach to manage them successfully. A thorough knowledge of the coagulation cascade along with a high-degree of suspicion and early recognition of coagulation is required. Abnormalities are critical for a timely intervention. Point-of-care tests like thromboelastography (TEG) as well as platelet function studies helped us arrive at an early diagnosis and initiate prompt treatment.
Keywords: thromboelastography; thrombin activatable fibrinolysis inhibitor; selective serotonin reuptake inhibitor